Implementasi Structure Learning Approach dalam Pengembangan Kompetensi Sosial Peserta Didik - Sukma Ayu Putri Titah Dewi; Arbin Janu Setyowati; Yuliati Hotifah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the implementation of the Structure Learning Approach (SLA) in developing students' social competence. Social competence is an important aspect of learning that supports students' ability to interact effectively, empathetically, and collaboratively in both school and community environments. The Structure Learning Approach emphasizes order and integration in the learning process, where students are guided to understand the relationships between concepts systematically through structured learning stages. This research employs a systematic literature review method by examining various sources from relevant national and international journals on the application of SLA in educational contexts. The findings indicate that the implementation of the Structure Learning Approach can enhance students' abilities to communicate, cooperate, and manage conflicts constructively. Furthermore, SLA also promotes active and reflective learning, which strengthens students' social-emotional skills. The implications of this study are expected to serve as a reference for educators in integrating the SLA approach to effectively develop social competence in school environments.